COMPARISON IN LEADERSHIP IN PRIVATE AND PUBLIC UNIVERSITY IN INDONESIA (TAKING FACULTY MEMBERS’ PERSPECTIVES) - Budiman, Muhammad Arief; Wu, Ming Chang; Asri, Sarwi (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2025)
Leadership in Indonesian universities faces significant challenges due to diverse regulatory frameworks, funding sources, and societal expectations. The research aims to identify the distinct challenges and approaches that university leaders face within the public and private sectors, providing insights into tailored leadership models. The study adopts a qualitative research method, using case studies of five lecturers from both public and private universities in Indonesia. Data was collected through semi-structured interviews, supplemented by document analysis of university policies, organizational structures, and academic performance reports. The purposive sampling approach ensures representation of universities from different regions and institutional scales, enabling an in-depth comparison between the leadership practices in public and private universities. The findings indicate that public university leaders often face bureaucratic constraints, while private university leaders prioritize financial stability and competitive positioning. This study concludes that effective leadership in Indonesian universities requires adaptability, innovation, and collaboration.